Implementation of a Novel Nature Inspired Firefly Optimizer for Power System Stability Enhancement - et. al., Dr.R.Shivakumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Enhancement of stability in interconnected power systems is a vital task in recent years. This paper provides a best solution to mitigate the low frequency inertial oscillations in a multimachine network, thereby enhance the system stability. An optimization criterion based on generator speed and load angle is developed with constraints to optimize the controller parameters required for closed loop model of the system. The controller is tuned using a novel nature inspired Improved Firefly Optimization Algorithm (FOA) and the simulation results of the proposed FOA based controller is compared and analyzed with that of Traditional controller and Genetic Algorithm based controllers to confirm the best performance of the proposed controller in enhancing the system stability.